Potters and vessels: consumers, markets and dynamics at play in the circulation of Gaulish terra sigillata: the evidence for the region under the influence of Olisipo (Lisbon) - Silva, Rodrigo Banha da (2021)
South Gaulish terra sigillata made its appearance in Portuguese Lower Tagus river valley area at its earliest stages, succeeding its italic predecessor. The author focused its approach in market conditions: regional settlement characteristics, including demographical dimension of urban centres, cultural background of populations and communication networks at place. On the other hand, vessel circulation patterns were considered on the base of potter´s stamps. Quantitative data was addressed, showing the main role played in redistribution by Lisbon, and the almost exclusivity of La Graufesenque imports. Potter´s stamps suggest different circulation for the region when compared to provincial capital, Mérida. Chronological data obtained demonstrated that the floruit of south Gaulish imports occurred in the period 40-65 AD, suffering after a complementary competition by Hispanic productions. In spite of this, imports from the big Gaulish centre persisted until circa 120 AD.